The Effect of Parasitic Rings and Ground Plane on Helix Strip Antenna - Muchammad Rofiq Fajar Setiawan; Aryo Baskoro Utomo (IJITEE (International Journal of Information Technology and Electrical Engineering), 2020)
Strip helix antennas offer better performance at wide bandwidth and more compact in size than conventional helix antennas. However, strip helix antennas have a relatively low gain compared to conventional helix antennas. In this paper, a strip helix antenna with 2.4 GHz frequency was designed, simulated, fabricated, and measured. This strip helix antenna was added with several parasitic rings, and its ground plane size was reduced to increase the gain value and its performance. The best simulation results according to the desired parameters were with return loss < -10 dB of -10.366 dB, VSWR < 2 of 1.8702, and directional radiation pattern of 66.5° beamwidth angle. However, the gain did not match with the desired parameters > 12 dB with the result of 8.9612 dB. Measured results showed that the helix strip antenna has a return loss of -10.37 dB and VSWR of 1.870. The parasitic rings addition can increase the strip helix antenna gain of 0.0201 dB and improves performances of return loss, VSWR, and bandwidth. Despite that, the ground plane size reduction actually decreases the gain value.